KONFLIK TANAH ULAYAT (Studi Kasus Konflik Tanah Ulayat Masyarakat Adat Pasukuan Tanjung Manggopoh Dengan PT. Mutiara Agam, Kabupaten Agam) - , Egie Pratama Mulya, Miftah Adhi Ikhsanto, Mi.OP ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This thesis discusses the customary land conflict between indigenous peoples and the company. The customary land conflicts between indigenous peoples of Tanjung Nagari Manggopoh with PT. Mutiara Agam has lasted in long duration. Various efforts have been done to manage and resolve this problem, ranging from the mediation process until it is brought into the realm of law. The process of conflict resolution in during time seems failure, because it has not been able to create peace and agreement between each actor on the conflict. This is a case study, because the conflict case in the present context and the escalation of the conflict has been continueing until today. This study systematically explores the information about the conflict of communal land to find out how the conflicâs pottrait and conflict resolution is done. Theories used in photographing the conflict in whole is a conflictâs theory, conflicts over natural resources, conflict of lands, conflict resolutions, and conflict resolution strategies. The customary lands conflict of Pasukuan Tanjung Manggopoh with PT. Mutiara Agam has lasted in long duration. The conflict has become more protracted because of the conflict resolution had failed to reach consensus as a foothold in a genuine peace. The fundamental difference between the customary law with formal law is like the distinction between oral tradition to written tradition that has been strong reasons in viewing the failure of customary land conflict resolution. The government has no clear legal tools to legitimize customary rights of indigenous peoples orally and it is unrecognized in the formal legal system. It needs a regulation from the Government as a relational bridge between the two power laws. In general, the portrait of the conflict of customary land Pasukuan Tanjung Manggopoh with PT. Mutiara Agam has the complex actors. Many actors stand below the surface of the main actors that reproduce the new conflict as an impact of major conflicts drag on. Dynamics, escalation of long duration and complexity of the actor have created the conflict run into the issue shifting and also the layered structure of conflicts. Primarily issue of conflict is because of threatened identity then shifted into conflict of social, economic, and political interests from the whole actors.